Assess and analyze : discovering the waste consuming your profits - Protzman, Charles; Whiton, Fred; Kerpchar, Joyce (BASICS Lean implementation series, 2023)
Lean is about building and improving stable and predictable systems and processes to deliver to customers high-quality products/services on time by engaging everyone in the organization.